PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN OPINI AUDIT ATAS LAPORAN KEUANGAN TERHADAP KINERJA KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA TIMUR - Lita Permata Sari; Nanik Hariyana (Relawan Jurnal Indonesia, 2017)
Public sector reforms in response to the criticism of inefficiency, unproductive, always loss, low quality, lack of innovation and creativity. To see the existence of the public sector in financial management, in particular the financial performance of local governments, this study will look at the effect of the Local Revenue earned by each region in 38 districts / cities in East Java and Audit Opinion provided by the Supreme Audit Board of the financial statements local government financial performance. The purpose of this study to determine whether there is influence of local revenue and audit opinion on the local government financial performance. This research uses multiple regression analysis with software SPSS 22. The results of research, analysis describes the local revenue and audit opinions have no effect on financial performance local governments in 38 districts / cities in East Java.